2019
DOI: 10.1186/s12871-019-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with intranasal dexmedetomidine decreases barbiturate requirement in pediatric patients sedated for magnetic resonance imaging: a retrospective study

Abstract: Background Barbiturates are commonly used in ambulatory sedation of pediatric patients. However, use of barbiturates involve risks of respiratory complications. Dexmedetomidine, a highly selective α 2 -adrenoceptor agonist, is increasingly used for pediatric sedation. Premedication with intranasal (IN) dexmedetomidine offers a non-invasive and efficient possibility to sedate pediatric patients undergoing magnetic resonance imaging (MRI). Our hypothesis was that dexmedeto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…With respect to safety, our results are in line with previous reports [12,29,32], since no patients who received dexmedetomidine intranasally in premedication had significant hemodynamic effects.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to safety, our results are in line with previous reports [12,29,32], since no patients who received dexmedetomidine intranasally in premedication had significant hemodynamic effects.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is of major relevance, since the use of dexmedetomidine has been poorly explored to date in pediatric patients subjected to combined anesthesia. Moreover, this observation indirectly shows a relationship between regional anesthesia and reduced ED occurrence, which might be attributed to the decreased need for volatile anesthetic, a known risk factor for ED [28].With respect to safety, our results are in line with previous reports [12,30,34], since no patients who received dexmedetomidine intranasally in premedication had significant hemodynamic effects. Moreover, at the same time, the administration given in advance compared with the intravenous one can avoid the delay in recovery from anesthesia and in length of staying in surgical area [17].…”
Section: Discussionsupporting
confidence: 91%
“…Dexmedetomidine is a high-affinity 2-mimetic drug. In particular, this molecule acts in the locus coeruleus determining a sedation pattern similar to natural sleep, without determining respiratory depression [12][13][14]. Recent studies suggest, among the remedies against ED, the use of dexmedetomidine intranasally as a premedication [10,11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of dexmedetomidine is its high transmucosal bioavailability of 65-80% [ 37 , 38 ]. Intranasal dexmedetomidine can induce sedation within 30 min in pediatric patients [ 2 , 5 , 6 , 9 , 11 , 12 , 14 22 , 24 , 26 28 , 31 , 35 , 36 , 38 , 39 ] .A recent study reported that intranasal dexmedetomidine 4 μg/kg enabled magnetic resonance imaging (MRI) examination without apnea and hypoxemia in infants [ 27 ]; however, 30.7% (16/52) of the patients developed bradycardia (< 80% of the baseline heart rate) and 3.8% (2/52) developed hypotension (< 80% of the baseline mean arterial pressure). As such, intranasal dexmedetomidine alone can be associated with slow onset time, bradycardia, or hypotension.…”
Section: Introductionmentioning
confidence: 99%